Operationalizing Identity – Studying Changing Selves in Experimental Learning Environments: A Commentary to the Special Issue. Issue 3 (3rd July 2021) - Shaffer, David Williamson
Abstract: This paper explores methodological questions in the study of identity through an examination and discussion of the empirical papers in this special issue. Particular attention is paid to the ways identity is operationalized in the study of how learning environments foster changes in students' sense of self. The paper concludes that identity is a difficult construct to study in the context of learning environments because it is simultaneously performative and subjective, and these dual aspects of identity may be best operationalized in an interactional view, in which identity is conceptualized as a set of relations between aspects of identity rather than as a state that can be coded directly in data on learning.